Construal of English Prepositions in, on, and at - Kusumastuti, Ria Apriani (Magister Kajian Bahasa Inggris (English Language Studies) Universitas Sanata Dharma Yogy, 2018)
The use of English preposition is a little bit confusing, especially for Indonesians. It is because Indonesia only has one preposition di- to indicate the English prepositions in, on, and at. In this research, it is found that the prepositions in, on, and at are used differently based on the relation between the object and the landmark. For preposition in, the concept of containment is introduced. This preposition is used when the object is surrounded by the landmark. For preposition on, the concept of contact and support is highlighted, and gravity takes part in the use of this preposition. It means that the object should be in contact with the landmark and the landmark should support the object so that it will not move or fall. Lastly, the preposition at requires us to portray an imaginary location to determine a certain point of the object. By using the correct preposition in, on, and at, one can have linguistic knowledge, and be able to avoid ambiguity to convey correct messages or ideas to the interlocutors. Keywords: cognitive semantics, prepositions, in, on, at, principles